Mechanistic relationship between the vagal afferent pathway, central nervous system and peripheral organs in appetite regulation - Ueno, Hiroaki (J Diabetes Investig, 2016)
The hypothalamus is a center of food intake and energy metabolism regulation. Information signals from peripheral organs are mediated through the circulation or the vagal afferent pathway and input into the hypothalamus, where signals are integrated to determine various behaviors, such as eating. Numerous appetite‐regulating peptides are expressed in the central nervous system and the peripheral organs, and interact in a complex manner. Of such peptides, gut peptides are known to bind to receptors at the vagal afferent pathway terminal that extend into the mucosal layer of the digestive tract, modulate the electrical activity of the vagus nerve, and subsequently send signals to the solitary nucleus and furthermore to the hypothalamus. All peripheral peptides other than ghrelin suppress appetite, and they synergistically suppress appetite through the vagus nerve. In contrast, the appetite‐enhancing peptide, ghrelin, antagonizes the actions of appetite‐suppressing peptides through the vagus nerve, and appetite‐suppressing peptides have attenuated effects in obesity as a result of inflammation in the vagus nerve. With greater understanding of the mechanism for food intake and energy metabolism regulation, medications that apply the effects of appetite‐regulating peptides or implantable devices that electrically stimulate the vagus nerve are being investigated as novel treatments for obesity in basic and clinical studies.